2022
DOI: 10.3390/biomedicines10071730
|View full text |Cite
|
Sign up to set email alerts
|

Significant Decrease in Glycated Hemoglobin, 2h-Post-Load Glucose and High-Sensitivity C-Reactive Protein Levels in Patients with Abnormal Body Mass Index after Therapy with Manual Lymphatic Drainage

Abstract: The objective of this study was to investigate the effect of manual lymphatic drainage (MLD) on the insulin resistance parameter (HOMA-IR), glycated hemoglobin (HbA1c), C-peptide, insulin, fasting plasma glucose (FPG), 2h-post-loadglucose (2h-PG) and the concentration of high-sensitivity C-reactive protein (hsCRP) in patients with abnormal body mass index. The study involved 30 patients, including patients with normal body weight (as a control group; group I; n = 14), overweight patients (group II; n = 9) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…These results are consistent with the results of our previous study [ 32 ], which showed that 10 × 30 min sessions of MLD significantly contributed to a decrease in 2h-PG levels (by 12 mg/dL) in overweight patients. To our knowledge, in the available literature no other studies have analyzed the effect of MLD on the level of 2h-PG in people with abnormal body weight [ 32 ]. Despite different therapeutic techniques being applied, a similar effect on the level of 2h-PG was demonstrated by Xie et al [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results are consistent with the results of our previous study [ 32 ], which showed that 10 × 30 min sessions of MLD significantly contributed to a decrease in 2h-PG levels (by 12 mg/dL) in overweight patients. To our knowledge, in the available literature no other studies have analyzed the effect of MLD on the level of 2h-PG in people with abnormal body weight [ 32 ]. Despite different therapeutic techniques being applied, a similar effect on the level of 2h-PG was demonstrated by Xie et al [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…It should be added that in our group of patients from the control group (without MLD intervention), we observed an increase in leptin concentration by 1.3 ng/mL at stage 1′ compared to stage 0′. Based on our own research [ 14 , 32 ] and the available literature [ 68 , 69 , 70 ], we suggest that the use of MLD therapy may improve biochemical parameters, and MLD therapy may be related to the improvement of the lymphatic system’s function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations